Crescimento e produção de Pinus caribaea var caribaea no Sudoeste Mato-Grossense - Mamoré, Fernanda Meyer Dotto (2016)
The objective of this study was to evaluate the growth and yield through statistical models about the variables of Dbh, total height and volume of a stand of Pinus caribaea var. caribaea 35, established under the initial spacing of 3 x 3 meters, located in the village of New Maryland, Southwest region of the State of Mato Grosso. The population under study was not buffed or subjected to any silvicultural treatment. Diameter were collected data to 1.30m high and the total height of 31 temporary plots with 900 m2 (30m x 30m) and carried out the killing of 60 dominant trees and codominant. In that 31 were rigorously scaled by Smalian method and 29 held the stem analysis. Data were submitted to normality test Shapiro Wilk; Also, the Pearson correlation was found between the variables, diameter, height and volume. fourteen volume equations were adjusted; Classified local productivity, and setting the nine models of forest growth and production. The verification of the accuracy of all tested models estimates were given, the adjusted determination coefficient (R2aj.); the standard error of the estimate (Syx%); and the percentage error (Error%) arranged graphically. For determining the volume of P. caribaea. caribaea, the best fit was obtained with the Schumacher-Hall model. The growth and yield models suitable for the P. caribaea diameter of the estimates was Hoerl, height and volume was the Moissev. In the classification of local productivity, we were determined site in 3 classes ranging between 18 and 26 m in 35-year-old content to the model of Moissev.